Interworking between IP security and performance enhancing proxiesfor mobile networks. - Assaf, N. (IEEE Communications magazine)
This article proposes the interworking between performance enhancing proxies (PEPs) and IPsec in mobile networks. The low-throughput problem due to TCP/IP in a radio access network is illustrated. Performance comparison among different PEPs implemented in the RAN is carried out in order to optimize the spectrum efficiency. By using PEP, end-to-end security is compromised, and we propose a concept to circumvent this problem. Furthermore, we propose a way to utilize PEP for different network loads. We suggest a scheme that allows the coexistence of IPsec and PEP over mobile networks, through adding an intelligent module in the node where the PEP is implemented